APLIKASI PERHITUNGAN BERAT BADAN IDEAL MENGGUNAKAN METODE IMT BERBASIS ANDROID - Ade Setiawan; Tika Adilah M; Muhammad Muharrom; Musriatun Napiah (Yayasan Akrab Pekanbaru, 2019)
Knowledge of normal weight is very important. Many general public whose lifestyle is unhealthy and irregular. One pattern of unhealthy living is excessive consumption of food. So that the height and weight are not balanced. When we consume too much food excessively, this can cause obesity. Because various kinds of diseases arise due to obesity problems. So from this we the authors make an android-based application whose function is to socialize the importance of ideal body weight. Of course many methods are used to find out the ideal weight category. Here the author uses the IMT (Body Mass Index) method to calculate and determine the ideal weight category and the tools used are eclipse indigo.